2022
DOI: 10.1108/yc-08-2021-1367
|View full text |Cite
|
Sign up to set email alerts
|

I give discounts, I share information, I interact with viewers: a predictive analysis on factors enhancing college students' purchase intention in a live-streaming shopping environment

Abstract: Purpose Grounding the research in the stimulus-organism-resource (S-O-R) framework, this study aims to address the research gap of explaining and predicting the relationship between price discounts, interactivity and professionalism on college students’ purchasing intention in live-streaming shopping. It also attempts to understand if trust plays the role of mediator in the effect of these relationships. Design/methodology/approach This study collected data using a questionnaire protocol adapted and refined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 64 publications
(123 reference statements)
5
34
0
3
Order By: Relevance
“…This may because consumers' purchase intention is increased by trust in streamers is through the improvement in consumers' trust in products [20]. Zhong et al (2022) got the similar results with Chen et al (2020) [9]. Lee and Chen (2021) found that streamer's expertise can positively affect consumers' perceived enjoyment which inspired impulse purchase [4].…”
Section: Streamer's Expertisementioning
confidence: 56%
See 3 more Smart Citations
“…This may because consumers' purchase intention is increased by trust in streamers is through the improvement in consumers' trust in products [20]. Zhong et al (2022) got the similar results with Chen et al (2020) [9]. Lee and Chen (2021) found that streamer's expertise can positively affect consumers' perceived enjoyment which inspired impulse purchase [4].…”
Section: Streamer's Expertisementioning
confidence: 56%
“…The results show that price discounts can not only increase collage students' trust to live streaming shopping, but can significantly improve their purchase intention. This was due to limited purchasing power among college students [9]. However, there are still researches show that price promotion will not promote consumers' purchase intention and buying behaviour.…”
Section: Price Promotionmentioning
confidence: 99%
See 2 more Smart Citations
“…The desire to trust the seller and take action where doing so puts the consumer exposed to the seller is referred to as consumer trust in online commerce. [18]. The human ego is built to be a consumer that constantly seeks approval and respect [19].…”
Section: Introductionmentioning
confidence: 99%